1992
DOI: 10.1038/bjc.1992.236
|View full text |Cite
|
Sign up to set email alerts
|

The prognosis of breast cancer patients in relation to the oestrogen receptor status of both primary disease and involved nodes

Abstract: Summary Nodal involvement is accepted as the best single marker of prognosis in breast cancer. However, there is little information on the sub-division of node-positive patients according to the oestrogen receptor status of the nodal tissue. We have previously reported (Eur. J. Ca. 1987, 23, 31) that, in almost all cases, involved nodes are only oestrogen receptor positive (ER+) Collaborative Group, 1988) and, in many countries, nodeinvolved, premenopausal patients are all treated with firstline chemothera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

1993
1993
2007
2007

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…The authors showed that primary tumours which were uniformly receptor positive mostly (27/29) gave rise to receptor‐positive nodes, whereas heterogeneous primaries most likely (17/20) gave rise to receptor‐negative nodes. In another study by Castagnetta et al (19), among 30 patients with uniformly positive ER across the primary biopsy, 28 had uniformly positive and two had completely negative nodes for ER. Among 24 patients with heterogeneous (+/–) primaries for ER, three had uniformly positive, seven had heterogeneous and 14 had completely negative lymph nodes.…”
Section: Discussionmentioning
confidence: 94%
“…The authors showed that primary tumours which were uniformly receptor positive mostly (27/29) gave rise to receptor‐positive nodes, whereas heterogeneous primaries most likely (17/20) gave rise to receptor‐negative nodes. In another study by Castagnetta et al (19), among 30 patients with uniformly positive ER across the primary biopsy, 28 had uniformly positive and two had completely negative nodes for ER. Among 24 patients with heterogeneous (+/–) primaries for ER, three had uniformly positive, seven had heterogeneous and 14 had completely negative lymph nodes.…”
Section: Discussionmentioning
confidence: 94%
“…Accordingly, unstimulated THP-1 cells were found to be ER negative by ICA. The signi®-cance of type I ER stems from the original de®nition of biochemical and functional features relevant to distinct sites of estrogen binding [Clark and Peck, 1979] and, more is illustrated by its discriminant value in the prognosis and treatment of both breast and endometrial cancer patients [Castagnetta et al, 1987a[Castagnetta et al, , 1992. We report that the phorbol diester TPA induces the appearance of type I ER in the soluble fraction of THP-1 cells and increases nuclear type I ER content.…”
Section: Discussionmentioning
confidence: 95%
“…This is worth noting since, in our own and other's experience, type I receptors only can be considered functional. In particular, the significance of type I ER stems from the original definition of biochemical and functional features relevant to distinct sites of estrogen binding [Clark and Peck, 1979] and, more, is illustrated by its discriminant value in the prognosis and treatment of both breast and endometrial cancer patients [Castagnetta et al, 1987[Castagnetta et al, , 1992. Therefore, this PMA-induced change in both ER and AR status may suggest that the effects of sex steroids, notably estrogens, on cytokine production in PMA-differentiated U937 cells could be related to the increase of type I nuclear receptor and/or be combined to additional, non-receptorial mechanisms.…”
Section: Discussionmentioning
confidence: 99%